Sistem Pendukung Keputusan Mutasi Pegawai Menggunakan Metode Simple Additive Weighting pada Sekretariat Daerah Kabupaten Sragen - AMINTAS, ARI (Universitas Multi Data Palembang, 2025)
Employee transfers are an important part of managing human resources in government agencies. The transfer process is often carried out as an effort to improve performance, efficiency and distribute employees evenly across various work units. However, decision making in the transfer process can be a challenge because it involves many factors, such as performance, absenteeism, length of service and education. In the context of the Sragen Regency Regional Secretariat, this process requires a system that can assist decision makers in determining employees who are worthy of transfer objectively and precisely. For this reason, a Decision Support System (DSS) is needed which can assist policy makers in analyzing and selecting employees to be transferred. This research uses four variables which are analyzed using Simple Additive Weighting (SAW) so that employees with a final calculation value of 1 are obtained as employees who are worthy of being recommended for transfer.